UJI AKTIVITAS EKSTRAK ETANOL KULIT ARI BUAH JENGKOL (Pithcelobium jiringa) SEBAGAI BIOLARVASIDA NYAMUK (Aedes aegypti L.) - Noverda Ayuchecaria; Nida Munirah; Amaliyah Wahyuni; Eka Kumalasari; Ratih Pratiwi Sari; Siska Musiam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Larvasida is still the first line in the prevention of Dengue Hemorrhagic Fever (DHF) disease caused by Aedes aegypti L. mosquitoes. Indonesia itself as a tropical country has many beneficial plants, one of which is Pithcelobium jiringa pericarp. Until now, the use of pericarp is still lacking even though jengkol fruit peels contain secondary metabolites such as flavonoids, saponins, tannins and triterpenoids, which have larvacidal effects. The purpose of this study was to determine the activity of ethanol extract of Pithcelobium jiringa pericarp as biolarvasida of Aedes aegypti L. mosquitoes from LC50 values. The treatment concentration used in this study was concentrations of 10%, 30%, and 50%. Temephos 1% is used as a positive control. The concentration was then tested on 20 Aedes aegypti L. larvae. The results showed that there was a treatment effect (sig <0.05) on the number of larval deaths, which from the results of Tuckey's analysis showed that 30% and 50% concentrations and 1% Temephos showed significant differences in the number of test larvae deaths. The results showed that the extract was effective as biolarvasida of Aedes aegypti L. mosquitoes. The results of probit analysis showed LC50 extract to Aedes aegypti L. larvae was 20.4716% which is a low toxin group in aquatic environments.